Hybrid integrated ultra-low linewidth coil stabilized isolator-free widely tunable external cavity laser - David A. S. Heim; Debapam Bose; Kaikai Liu; Andrei Isichenko; Daniel J. Blumenthal (Nature Communications)
Abstract Precision applications including quantum computing and sensing, mmWave/RF generation, and metrology, demand widely tunable, ultra-low phase noise lasers. Today, these experiments employ table-scale systems with bulk-optics and isolators to achieve requisite noise, stability, and tunability. Photonic integration will enable scalable, reliable and portable solutions. Here we report a hybrid-integrated external cavity widely tunable laser stabilized to a 10 m-long integrated coil-resonator, achieving record-low 3 – 7 Hz fundamental linewidth across a 60 nm tuning range and 27 – 60 Hz integral linewidth with 1.8E-13 ADEV at 6.4 ms across 40 nm, delivering orders of magnitude frequency noise and integral linewidth reduction over state of the art. Stabilization is achieved without an optical isolator, leveraging resilience to optical feedback of 30 dB beyond that of commercial DFB lasers. The laser and reference cavity are fabricated in the same Si3N4 CMOS-compatible process, unlocking a path towards fully integrated visible to ShortWave-IR frequency-stabilized lasers.